PERANCANGAN SISTEM INFORMASI KEPEGAWAIAN DENGAN MODEL SYSTEM DEVELOPMENT LIFE CYCLE PADA KANTOR KELURAHAN CIMUNING - Abdul Ro’uf; Endang Retnoningsih (Institut Bisnis Muhammadiyah Bekasi, 2022)
In government agencies, computer technology is considered to be able to support the effectiveness, productivity, and work efficiency of employees and is very reliable in supporting every job in government agencies. The Cimuning sub-district office is one of the government agencies that continuously improve employee work effectiveness. Data collection on employee leave and employee permits needs optimization. The purpose of this research is to build a personnel information system using Visual Basic.Net programming which will provide solutions and convenience in processing data and searching employee data. This research method is SDLC waterfall model. The result of this information system is to make it easier for employees to search data and collect employee data.